Friday
March 24, 2017

Post a New Question

Posted by on Friday, February 29, 2008 at 6:53pm.

Assume that no denomenator equals 0.

(7x^2+3x-9)-(-x^2+8x-3)

= 7x^2+3x-9+x^2-8x+3
= (7x^2+x^2)+(3x-8x)+(-9+3)
= 8x^2+-5x+-6
= 8x^2-5x-6(answer)

  • Algebra II - , Friday, February 29, 2008 at 7:00pm

    What exactly is your question? I don't even see a denominator anywhere :)

    What you have is right so far. If you want to finish that question you need to use the quadratic formula

    x = (-b +/- square root(b^2 - 4ac)) / 2a

    x = (5 +/- square root (25 + 192)) / 16

    x = (5 +/- square root (217)) / 16

    which yields x1 = 1.23 and x2 = -0.61

  • Algebra II - , Friday, February 29, 2008 at 7:11pm

    (7x^2+3x-9)-(-x^2+8x-3) is the question. the rest is my work

  • Algebra II - , Friday, February 29, 2008 at 7:13pm

    Your solution is perfect, did you just want confirmation?

  • Algebra II - , Friday, February 29, 2008 at 7:17pm

    yes

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question